KESERIUSAN KECURANGAN AKUNTANSI DAN NIAT MENJADI WHISTLEBLOWER INTERNAL ANALISIS MODERASI EDUKASI - Astia Putriana; M. Riduan Abdillah (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2022)
Fraud is a major disaster for organizations. Employee participation to blow the whistle is a hope for every organization. This study aims to examine the effect of seriousness of fraud in accounting on the intention to become an internal whistleblower and the moderation effect of educational on the intention to become an internal whistleblower. The object of this research is civil servants (ASN) in the finance department of the Banjarmasin City Government. The sampling technique used is the saturation technique, which uses the entire population as the research sample. There are 100 respondents obtained for samples. Questionnaire data were analyzed using Partial Least Squares (PLS) analysis tool. The results showed that the seriousness of fraud in accounting had an effect on the ASN's intention to become an internal whistleblower. However, education is not able to moderate the influence of seriousness of fraud in accounting on the intention to become internal whistleblower. These results contribute to providing new insights related to policies that are able to encourage ASN to become internal whistleblower. Keywords: Seriousness of fraud in accounting; education; intention to become an internal whistleblower